Drosophila brca2 is required for mitotic and meiotic DNA repair and efficient activation of the meiotic recombination checkpoint. - Martha Klovstad; Uri Abdu; Trudi Schüpbach (PLoS Genetics)
Heterozygous mutations in the tumor suppressor BRCA2 confer a high risk of breast and other cancers in humans. BRCA2 maintains genome stability in part through the regulation of Rad51-dependent homologous recombination. Much about its precise function in the DNA damage responses is, however, not yet known. We have made null mutations in the Drosophila homolog of BRCA2 and measured the levels of homologous recombination, non-homologous end-joining, and single-strand annealing in the pre-meiotic germline of Drosophila males. We show that repair by homologous recombination is dramatically decreased in Drosophila brca2 mutants. Instead, large flanking deletions are formed, and repair by the non-conservative single-strand annealing pathway predominates. We further show that during meiosis, Drosophila Brca2 has a dual role in the repair of meiotic double-stranded breaks and the efficient activation of the meiotic recombination checkpoint. The eggshell patterning defects that result from activation of the meiotic recombination checkpoint in other meiotic DNA repair mutants can be strongly suppressed by mutations in brca2. In addition, Brca2 co-immunoprecipitates with the checkpoint protein Rad9, suggesting a direct role for Brca2 in the transduction of the meiotic recombination checkpoint signal.